An improved method for measuring wetting front advancing velocity. Issue 6 (27th October 2021) - Liu, Qiang; Xi, Ping; Liu, Guojun; Miao, Jiali; Liu, Fengzhu
Abstract: The unsaturated soil hydraulic conductivity function is one of the keys to solving unsaturated seepage issues. The wetting front advancing method (WFAM) is a proposed method for quickly measuring the coefficient of permeability of the unsaturated soils, but it has some demerits and limitations. In this study, a series of capillary rise tests were conducted and the coefficient of permeability of six kinds of unsaturated soils were obtained by using the WFAM. Based on the analyzing of characteristic changes in volumetric water content via soil moisture sensors in the capillary rise test, improvements were made to the method of determining the wetting front advancing velocity. The RMSE evaluation index was used to analyze the deviation of the data obtained by the improved method from the original visual method. The RMSE of the wetting front advancing velocity ranged from 0.0007 to 0.0074 cm s –1, and the RMSE of the coefficient of permeability ranged from 0 to 5.2 × 10 –6 m s –1 . The results indicated the applicability of the improved method. Core Ideas: We provide an improved method for measuring wetting front advancing velocity. We provide a fast and automatic method for measuring the hydraulic conductivity of unsaturated soils. A reference for the automatic measurement of soil permeability is proposed.